Genetic types, mineralization styles, and geodynamic settings of Mesozoic tungsten deposits in South China - Zhao, Wen Winston; Zhou, Mei-Fu; Li, Yan Hei Martin; Zhao, Zheng; Gao, Jian-Feng (Journal of Asian earth sciences, 2017)
[Display omitted] •Skarn, porphyry, greisen and quartz-vein types of W deposits are associated with the Mesozoic magmatism in South China.•The Mesozoic W deposits are mainly distributed in the E-W-trending Nanling region and the NE-trending Yangtze River region.•Four episodes of the W mineralizations were related to the closure of paleo-Tethys and subduction of the paleo-Pacific plate.•The distribution of the Mesozoic W deposits resulted from the break-off and anticlockwise rotation of the subducted ridge. South China hosts the most abundant and largest tungsten (W) deposits in the world, being a famous W metallogenic region. Located at the eastern part of the South China Block, which was formed by amalgamation of the Yangtze and Cathaysia Blocks during the Neoproterozoic, these W deposits were mainly formed during the Mesozoic. The W mineralization is dominanted by greisen, quartz-vein, skarn, and porphyry types, all of which are genetically related to the evolution of highly fractionated granitoids. Four episodes of W mineralization are recognized: (1) Late Triassic (230–210Ma) in the central and western parts of South China; (2) Middle Jurassic (ca. 170Ma) to Early Cretaceous (ca. 140Ma) in the interior of South China, with the mineralization being concentrated in southern Jiangxi Province between 165 and 150Ma; (3) Early Cretaceous (136–120Ma) with deposits across South China; and (4) Late Cretaceous (100–80Ma) mainly in the southwestern parts of South China. These four periods of mineralization are closely related to the closure of paleo-Tethys and subduction of the paleo-Pacific plate. In the Late Triassic, these two events caused local extensional environments, facilitating emplacement of the peraluminous granitoids, and formation of the W deposits. In the Middle Jurassic, break-off of the subducting oceanic plate resulted in emplacement of highly fractionated granites in the Nanling region. Later anticlockwise rotation of the paleo-Pacific plate created widespread S-type granitoids and associated Middle Jurassic to Early Cretaceous W mineralization in the interior of South China. Since 136Ma, rollback of the subducting Pacific plate resulted in weak W mineralization across South China. Finally, a change of direction in the retreating plate from SE to ESE resulted in intensive mineralization of the southwestern part of South China.